Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.14814/phy2.13378
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 dose-dependently stimulates proliferation and cadherin-11 expression via ERK and p38 in a murine metanephric mesenchymal cell line

Abstract: BMP7 is expressed in ureteric buds and cap mesenchyme of the fetal kidney, mediating branching morphogenesis and survival and priming of metanephric mesenchyme. Although dose‐dependent effects of BMP7 in collecting duct cells have been reported, studies in metanephric mesenchymal cells are lacking. We examined the effects of BMP7 on MAP kinase activation, proliferation, and expression of cadherins in a metanephric mesenchymal cell line MS7 by thymidine incorporation, immunoblot analysis, and quantitative real‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Our studies revealed that proteins known to be related to BMP7 signaling, such as MAPK14 24,25,[34][35][36][37] , were expressed differently in resistant tumors than in parental tumors. Because MAPK14 is known to be regulated by BMP7 23,24 via SMAD activation 25 , we focused on this protein for validation studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our studies revealed that proteins known to be related to BMP7 signaling, such as MAPK14 24,25,[34][35][36][37] , were expressed differently in resistant tumors than in parental tumors. Because MAPK14 is known to be regulated by BMP7 23,24 via SMAD activation 25 , we focused on this protein for validation studies.…”
Section: Discussionmentioning
confidence: 81%
“…Because MAPK14 is known to be regulated by BMP7 23,24 via SMAD activation 25 , we focused on this protein for validation studies. BMP7 can either promote or inhibit MAPK14 activation depending on the cellular context and BMP7 dose [23][24][25]36 . Here, we found that BMP7 specifically regulated MAPK14 at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The next GO term describes a quite significant biological process, the regulation of metanephric cap mesenchymal cell proliferation ( GO:0090095 ). As a tissue specific biological process, the involvement of this GO term in various tumor associated genes, such a cadherin family, p38, and MYC, has been confirmed [ 84 , 85 ] In cancers, particularly renal carcinoma, genes that contribute to GO:0090095 have been reported to be up-regulated compared with other irrelevant genes [ 86 ], thereby conforming to the expression profile clustering function of such a GO term. GO:0004872 , which describes the general receptor activity, may have also been enriched by genes with high or low expression patterns.…”
Section: Discussionmentioning
confidence: 95%
“…BMP7 was previously reported as an activator of the non-canonical BMP effectors MEK and ERK kinases. 35 , 36 MEK- and ERK-signaling pathways were shown to regulate normal OPC migration. 37 , 38 As expected, exogenous rBMP7 rapidly activated the phosphorylation of canonical BMP signaling effectors SMAD1/5/9 in both poorly- and highly invasive models ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%